Epistemic orientation toward teaching science for knowledge generation: Conceptualization and validation of the construct. Issue 9 (25th March 2022) - Suh, Jee Kyung; Hwang, Jihyun; Park, Soonhye; Hand, Brian
Abstract: Research in science education has emphasized the importance of knowledge generation approaches to learning. Creating generative learning environments requires teachers to address the epistemic underpinning of science practices and shift their orientations toward knowledge generation approaches. This study aimed to propose epistemic orientation as a key component of teacher development for implementing knowledge generation approaches and develop an empirically grounded model of the construct through a mixed‐method approach. Epistemic orientation toward teaching science for knowledge generation (EOTS‐KG) was defined as a particular direction of thinking concerning how to deal with knowledge and knowledge generation processes when a teacher aims to create generative learning environments for teaching science. Building on the theoretical model of EOTS‐KG established through a critical literature review, we conducted a multiple case study of exemplary elementary teachers and designed an instrument called the Epistemic Orientation Survey. The model from the case study described four major subdimensions indicated by 11 essential elements that should be considered when preparing teachers for implementing a knowledge approach, suggesting that teachers' beliefs about learning should be a priority in teacher development. Using the instrument, we tested the dimensionality of the construct, leading to the suggestions that both unidimensional and multidimensional models are valuable for use in future research. We believe the model developed in this study would serve as a powerful framework to allow researchers to examine changes in teachers' epistemic orientation in various contexts.